Significance of Conjunctions and the Impact Thereby on Differences Muslim Scholars (Foqaha) - Mohammed Sami Saleh At-Taweel (My University, 2009)
Thank God alone and Prayers and Peace to Prophet Mohammad. This research discusses the subject of conjunctions semantically and structurally. I discussed in this research some of conjunctions like and, but, even, then, until, or This study was focused on the significance of these conjunctions in Muslim scholar opinions and to show the significance of these conjunctions. After that I showed some of the practical issues that show the impact of the significance of these conjunctions and in scholars opinions. For example, the conjunction and where many Muslim scholars were different in its significance on their opinions, arrangements, simultaneously, gathering. I found that the strongest opinion is arrangement some of the issues that caused by this difference is in the arrangement of purity organs.

الحمد لله والصلاة والسلام على رسول الله وبعد: فهذا البحث يتناول بابا من أبواب حروف المعاني وهو حروف العطف، وحروف المعاني غير حروف المباني، فالحرف إذا كان جزءاً من بنية الكلمة فهو حرف مبنى، وإذا دل على معنى في غيره فهو حرف معنى وقد تناولت في هذا البحث سبعةً من حروف العطف، وهي: الواو والفاء وثم وحتى وأو وبل ولكن. وتركزت الدراسة على دلالة هذه الحروف عند النحاة والأصوليين، وبيان أسباب الخلاف في دلالة بعض الحروف وبيان الراجح في ذلك. وبعد ذلك عرضت لبعض المسائل التطبيقية التي توضح أثر دلالة هذه الحروف في اختلاف الفقهاء. وتوصلت في هذه الدراسة إلى أن الراجح في دلالة الواو هو مطلق الجمع وفي الفاء الترتيب والتعقيب، وفي ثمالترتيب مع التراخي، وفي حتى الغاية، وفي أو الدلالة على أحد الشيئين أو الأشياء، وفي بل الإضراب، و في لكن للاستدراك.
دلالة حروف العطف وأثرها في اختلاف الفقهاء